Gender differences in income sources of the elderly in Peninsular Malaysia. - Masud, Jariah; Haron, Sharifah Azizah; Gikonyo, Lucy Wamuyu (Springer Verlag, 2008)
Objectives of this study were to identify and compare the sources and amounts of income received by elderly males and females. Specifically, this study examined gender differences in income receipt for a sample of 1,841 residents of Peninsular Malaysia who were aged 55-75. Significant differences were found in the source and amount of income of elderly males and females. Although the majority of elderly of both genders received income from their children, there were profound gender differences in the receipt of work-related and investment-related income.